Kajian Pelaksanaan Pelayanan Cakupan K4 Di Puskesmas Baumata Tahun 2018 - Manu, Neneng N. K .; Regaletha, Tadeus A. L.; Upa, Erny E Pua (Timorese Journal of Public Health, 2019)
K4 pregnant women services are complete antenatal services with a time of examination, namely one visit in the first trimester, one visit in the second trimester, and two visits in the third trimester. The Baumata Community Health Center experienced a decline in K4 coverage based on the Kupang District Health Office profile data and annual reports where in 2016 K4 coverage reached 60.7%, in 2017 it reached 51.8% and in 2018 it only reached 44.2%. This research is a combination of qualitative and quantitative research (mix method) with descriptive research. The purpose of this study is to examine the implementation of K4 coverage services at the Baumata community health center in 2018 which includes description of inputs (human resources, facilities, sources of funds, policies and Standard Operating Procedures), process descriptions (planning and organizing) as well as output descriptions (K4 coverage ). Informants in this study amounted to 13 people and respondents numbered 66 people consisting of the Head of the Family Health and Nutrition Section of the Kupang District Health Office, the Head of the Baumata community health center, the Midwife who provided K4 services and the mother who had a pregnancy (K4) at the community health center Baumata in 2018. The results showed that in terms of input at the Baumata community health center as a whole it was good but there was no Ultrasonography facility at the community health center and the limited space where there was no special room for maternal and child health services/ family planning/immunization, in terms of the process is good related to planning, organizing and forms of services received by pregnant women are in accordance with 10T standards, it's just a long time in the process of providing services due to poor management time and lack of awareness of pregnant women to check pregnancy to the facility. The nearest health bag is due to the lack of knowledge of pregnant women about the importance of antenatal care, while in terms of output based on document review it can be seen that in the past three years there has been a decline in achievement of the K4 target at the Baumata community health center. It is recommended that the Baumata community health center procure supporting facilities in the form of Ultrasonography and additional rooms, make time management so that pregnant women do not wait too long for the service process, and conduct socialization to the public about the importance of antenatal care.